The effect of sphingosine‐1‐phosphate on the endothelial glycocalyx during ischemia‐reperfusion injury in the isolated rat heart. (25th February 2020) - Araibi, Hala; van der Merwe, Elizabeth; Gwanyanya, Asfree; Kelly‐Laubscher, Roisin
Abstract: Objective: Sphingosine‐1‐phosphate is a natural metabolite that is cardioprotective, but its effects on endothelial glycocalyx damage during ischemia‐reperfusion are unknown. Therefore, we investigated the effect of sphingosine‐1‐phosphate on the endothelial glycocalyx during ischemia‐reperfusion. Methods: Isolated hearts from Wistar rats were perfused on a Langendorff system with Krebs‐Henseleit buffer and pretreated with sphingosine‐1‐phosphate (10 nmol/L) before ischemia‐reperfusion. Infarct size was measured by triphenyl tetrazolium chloride staining (n ≥ 6 per group). Cardiac edema was assessed by calculating total water content (n = 7 per group) and histologically quantifying the interstitial compartment (n ≥ 3 per group). The post‐ischemic coronary release of syndecan‐1 was quantified using ELISA. Syndecan‐1 immunostaining intensity was assessed in perfusion‐fixed hearts (n ≥ 3 per group). Results: Pretreatment with sphingosine‐1‐phosphate decreased infarct size in isolated hearts subjected to ischemia‐reperfusion ( P  = .01 vs ischemia‐reperfusion). However, sphingosine‐1‐phosphate had no effect on syndecan‐1 levels in the coronary effluent or on the intensity of the syndecan‐1 immunostaining signal in cardiac tissue. Heart total water content was not significantly different between control and ischemic groups but was significantly decreased in hearts treated with sphingosine‐1‐phosphate alone. Conclusion: These results suggest that sphingosine‐1‐phosphate‐induced cardioprotection against ischemia‐reperfusion injury is not mediated by the maintenance of syndecan‐1 in the endothelial glycocalyx.